IMPLIKASI PENERAPAN MODEL PEMBELAJARAN TRANSFORMATIF DALAMPEMBELAJARAN AGAMA DI PESANTREN - Ibrahim (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2019)
The transformative learning Model requires transforming institutional management, relationship patterns, and building critical and progressive minds among learners. Its application in Pesantren will give implications, both positive and negative, let alone the pesantren that has its own distinction and charisma. To present this writing, the authors use a descriptive approach and analysis of hermeneutics-philosophical, philosophical and theoretical approaches of psychological. Among the implications of Pesantren-from the plus side-is the progression of the management of the institution and the logical power, while the downside is the educational distinksi management pattern, Kiai and students relationship patterns as well as the development of liberal humanism, if applied in full. However, this can be minimized by the formulation of a collaborative and transactional learning implementation.